Different Growth and Physiological Responses of Six Subtropical Tree Species to Warming - Li, Yiyong; Zhou, Guoyi; Liu, Juxiu (Frontiers in Plant Science, 2017)
Quantifying changes in interspecific plant growth and physiology under climate warming will facilitate explanation of the shifts in community structure in subtropical forest. We evaluated the effects of 4 year climate warming (ca. 1°C, 2012-2015) on plant growth and physiological parameters of six subtropical tree species by measuring trees growing at high-elevation site and low-elevation site. We found that an increase in soil/air temperature had divergent effects on six co-occurred species. Warming increased the biomass of Schima superba and Pinus massoniana, whereas decreased specific leaf area and intrinsic water use efficiency compared to other species. Warming decreased the foliar non-structural carbohydrates for all species. Our findings demonstrated that a warmer climate would affect the physiology and growth of subtropical plants, but the responses were species-specific. Moreover, alterations in plant growth may lead to changes in the competitive balance and, ultimately, the composition of these forests.